2006
DOI: 10.4321/s0004-06142006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Registro español del sistema TRT Remeex en mujeres con incontinencia urinaria de esfuerzo

Abstract: The Reemex system is a minimally invasive technique with consistent results and even improved in heterogeneous groups of patients including intrinsic sphincter defficiency, reoperations, mixed incontinence and associated pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…According to abdominal leak point pressures, there were no patients with pressures lower than 60 cm H 2 O, which is consistent with ISD. In our study, we found a cure rate of 84.2%, which is consistent with other Remeex procedure series [17,18,19,20,21]. …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to abdominal leak point pressures, there were no patients with pressures lower than 60 cm H 2 O, which is consistent with ISD. In our study, we found a cure rate of 84.2%, which is consistent with other Remeex procedure series [17,18,19,20,21]. …”
Section: Discussionsupporting
confidence: 80%
“…Thirty-one patients were cured and the device was removed in 1 patient because of infection. Moreno Sierra et al [20] conducted a retrospective study of 683 patients with mixed urinary incontinence, ISD and recurrent SUI who underwent a Remeex procedure with a mean follow-up of 23 months. They reported a 92.2% cure rate, improvement in 6.9% and failure in 0.9% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The common postoperative complications are wound infection, vaginal erosion, and de novo urgency according to the reported studies. Moreno Sierra et al [8] reported that 1.7% of patients require detraction of the varitensor owing to persistent abdominal wall seroma, and 0.8% present with vaginal extrusion of the sling. Errando et al reported that no urethral or vaginal erosion occurred after the Remeex procedure, and they found only one patient (0.8%) with a seroma in the subcutaneous tissue around the varitensor.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients (7%) required sling tension readjustment. Moreno Sierra et al [8] studied a group of 683 women that consisted of patients with mixed incontinence (30.2%), ISD (73.1%), and recurrent SUI (35.7%); these patients underwent the Remeex treatment with a mean follow-up of 23 months (range, 6-93 months). Those authors reported that the cure rate was 92.2%, with 6.9% reporting improvement and 0.9% reporting failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation